The Application of the Experimental Method on Science Learning Outcomes of Grade 4 Students at SDN Inpres Nebura, Sikka - Hastrianti, Siti Serayu; Fitriah; Sada, Mariana (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2025)
This study investigates the effectiveness of the experimental method in enhancing science learning outcomes among grade 4 students at SDN Inpres Nebura, focusing on the topic of photosynthesis. Employing a descriptive quantitative design, the study involved all students at SDN Inpres Nebura, with a purposive sample of 14 grade 4 students. Data were gathered through questionnaires and documentation sheets. The findings reveal a notable improvement in learning achievement, as the mean score increased from 69.29 on the pre-test to 79.29 on the post-test. Additionally, the questionnaire results demonstrate that the majority of students expressed highly positive perceptions of the experimental method, with an average positive response rate of 99%. These results suggest that the experimental method is an effective pedagogical approach for improving student learning outcomes in elementary science education.